If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -6 = 48 Reorder the terms: -6 + 6x = 48 Solving -6 + 6x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 6x = 48 + 6 Combine like terms: -6 + 6 = 0 0 + 6x = 48 + 6 6x = 48 + 6 Combine like terms: 48 + 6 = 54 6x = 54 Divide each side by '6'. x = 9 Simplifying x = 9
| 9x+7=43 | | 9x+7=23 | | 7n+8=64 | | 6+2a=3 | | 5n-12=28 | | 5n+8=23 | | (n-9)*9=18 | | (n-8)*3=12 | | (n+1)*4=16 | | 7-2x=2x-7 | | (-22)(-22)= | | -22*-22= | | (-22)*(-22)= | | 7=7+7x | | 4x+5=9x-14 | | 5x+8=-42 | | (-9)(-1)(9)(-2)= | | 10n+10=100 | | 3n-14=10 | | 5n+10=20 | | (n-8)*10=90 | | (n-6)*4=24 | | (n+3)*2=14 | | -4z=-6 | | 10=x+0.8(9-x) | | .66a-.75=.75a | | .25x+.50=.25x-.50 | | 3-x=1 | | 3-y=5+y | | x-y=-8 | | x-y=7 | | 8x+6=-90 |